The lean-agile way unleash business results in the digital era with value stream management - Rupp, Cecil; Knaster, Richard; Pereira, Steve; Shalloway, Al (Packt Publishing Ltd., 2024)
Discover how mastering Lean, Agile, and VSM principles and practices can enhance your product delivery performance, mitigate risk, and foster business agility, giving you a competitive edge Key Features Learn how to apply Lean practices to eliminate waste and delays, ensuring value for your customers Master Agile practices to address problems and create value-centric products and services Explore VSM methods and tools to identify and prioritize improvement opportunities that maximize value addition Purchase of the print or Kindle book includes a free PDF eBook Book Description In the fast-paced business and IT landscape, efficiency is key to success. To excel in delivering value to customers, reducing waste, and resolving pain points, identifying the right tools and strategies is paramount. Unlocking the secrets of Lean, Agile, Value Stream Management (VSM), and various digital enhancements, this book offers a roadmap to optimize processes, improve products, and elevate service delivery. You'll start with an introduction to foundational Lean and Agile practices, recognizing the significance of digital enhancements in modernizing business processes. As you progress, you'll learn VSM techniques to identify and prioritize work and investments to provide maximum value to customers. Moreover, you'll grasp Lean-Agile practices aimed at promoting collaboration among teams and ensuring the continuous flow of product-oriented deliveries tailored to address customer needs. Finally, you'll gain executive-level insights on how organizations must access timely information for decision-making and foster a culture of continuous business transformation. Armed with this knowledge and a robust toolkit, you'll be empowered to drive meaningful change, optimize resources, and stay ahead in the rapidly evolving marketplace. What you will learn Understand how to integrate the seemingly disparate practices of Lean and Agile Integrate Lean, Agile, and VSM to accelerate value flow, enhance efficiency, and drive improvements Drive product-oriented transformations with business increments, Lean-Agile teams, product lifecycles, VSM, and IT alignment Leverage the VSM implementation roadmap to drive digital value stream enhancements Investigate advanced VSM tools/platforms, AI insights, and VSMP selection criteria Explore Lean-Agile/VSM success stories to gain implementation insights Who this book is for This Lean-Agile book is for business and technology professionals striving to optimize value delivery while minimizing costs. Whether you're a VSM manager, a member of a product delivery team, DevOps engineer, or an IT specialist, this book offers proven methods for effectively identifying and implementing improvement opportunities. Product owners looking to prioritize backlog items and corporate executives aiming to demonstrate positive returns on information technology investments will also find this book helpful.
Keywords: Information technology -- Management; Agile software development; Information technology projects -- Management; Technologie de l'information; Gestion; Méthodes agiles (Développement de logiciels); Projets de technologie de l'information; Gestion